Prarancangan Pabrik Propilena Oksida Dengan Proses Hydroperoxide Kapasitas 48.000 Ton/Tahun - Rahayu, Erlina Budi; , Ir. Herry Purnama, M.T., Ph.D; , Eni Budiyati, S.T, M.Eng (2015)
Propylene oxide factory with raw materials isobutanol, air and propylene with a capacity of 48,000 tons per year is planned to operate for 330 days per year. The process of making propylene oxide is carried out in a bubble reactor working continuously, which takes place on a liquid-gas phase, irreversible, exothermic, non-adiabatic, isothermal conditions 120C and pressure of 13.6 atm. And in a batch reactor with a stirred tank, which takes place in the liquid-liquid phase, with the catalyst MoO3 on 110C condition and pressure of 5.53 atm. This plant is classed high-risk factories. Isobutane requirement for this plant as much 41210.55517 kg per hour, 76843.47485 air requirements and needs as much propylene 4698.2550 kg per hour. Products such as Propylene Oxide 6060.606061 kg per hour, and TBA (Tert Butyl Alcohol) as 15603.25151 kg per hour. Utilities include water provision process support for 72813.8147 kg per hour obtained from river water, the provision of 8427.53 kg of saturated steam per hour compressed air requirement of 150 m3 per hour, the demand for electricity is obtained from the PLN and a generator set of 1,500 pieces kW in reserve, as 12608.3 liters of fuel per day. The factory was established in Cilegon, Banten, with a land area of 16 550 m2 and the number of employees 120 people. Propylene oxide mill uses fixed capital of Rp.387.860.798.576,94 and working capital of Rp.68.218.228.111,37 From the economic analysis of this plant show a profit before tax Rp.173.136.297.804,51 per year after taxes 30% profits reached Rp.51.940.889.341,35 per year. Percent Return On Investment (ROI) before tax after tax 44.64% and 31.25%. Pay Out Time (POT) before taxes for 1.83 years and 2.42 years after tax. Break Even Point (BEP) amounted to 41.94%, Shut Down Point (SDP) amounted to 26.39% Discounted Cash Flow (DCF) accounted for 49.4%. From the data above feasibility analysis concluded that the plant is profitable and feasible to set.